A prospective study of clinicopathological profile and outcome of otomycosis in patients presenting to a tertiary care center - Puthukudy, Preetham A.; Feshan, Musarrat; Muthu, Devipriya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Otomycosis is reported all over the world and it accounts for 5 to 20 percent of all cases of infective otitis externa during rainy seasons. The article’s main purpose was to study the predisposing factors, most common symptoms, different species of fungi involved, and the treatment outcome of otomycosis. A Chi-square test was used to analyze the association of various factors. Statistical package for the social sciences (SPSS) version 20 was used for statistical analysis. Methods: In this prospective observational study, 100 patients with clinical evidence of otomycosis were evaluated and data regarding age, gender, risk factors, clinical appearance, fungal culture, and treatment modality received were taken. Response to treatment at the 1st follow-up (at 1 week), 2nd follow-up (at 2 weeks), and 3rd follow-up (at 3 weeks) were statistically analyzed. Results: In our study we found the disease to be more common among the 51 to 60 years age group. Males were affected more than females. The most common occupation was housewife. The most common predisposing factor was ear picking and the symptom was otalgia followed by itching. The disease was predominantly unilateral. Aspergillus niger was found to be the most common organism. Clotrimazole was the effective drug for otomycosis and significant responses were seen at the end of the 3rd week of treatment. Conclusions: Aspergillus niger was the most common organism causing otomycosis and responded well with clotrimazole ear drops.